Negative Pressure Wound Therapy in the Treatment of Sternal Infection after Cardiac Surgery: a Case Report and Literature Review - Yulia V. Ivanova; Igor A. Kryvoruchko; Viktor M. Cheverda; Dmytro V. Minukhin; Svetlana Gramatiuk; Sergii I. Estrin; Andrii O. Kovalchuk (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To assess the effectiveness of negative pressure wound therapy (NPWT) in the treatment of sternal infection following heart surgery.Materials and methods. During 2019-2022, six patients aged from 46 to 69 years underwent NPWT for sternal infection which occurred within 2 to 24 weeks after complete median sternotomy. For the purpose of temporary wound closure, standard dressing kits with sorption sponge were used. Negative pressure was created by electric vacuum pump with a constant vacuum mode at a range of -75 to -115 mm Hg and a duration of 4-5 days per session. In all cases determination of serum procalcitonin, bacteriological examination of wound discharge, computed tomography (CT) of the chest were performed in dynamics.Results. The study revealed that NPWT in all cases promoted wound cleansing, gradual closing of fistulas and non-grooving pockets, termination of inflammatory process, reduction of the wound cavity, thus accelerating complete wound healing. A significant reduction in the level of wound contamination was revealed after the first NPWT session (below the critical level of 103 CFU), compared to that before treatment (107-108 CFU). Normalization of the level of procalcitonin in the blood serum was determined by day 5-7 of NPWT. CT showed the signs of sternum stability and reduction of inflammatory process in surrounding tissues after treatment. Each treatment case required from 2 to 4 sessions. The duration of hospital stay ranged between 25 and 35 days. A treatment case of one of the 6 patients included in the study is described.Conclusions. NPWT has proven to have positive clinical effect in the local treatment of postoperative sternal infection and can be applied as an ultimate or a transitional option. Methodology of its clinical application needs further elaboration.